1996
DOI: 10.1200/jco.1996.14.7.2083
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, placebo-controlled trial comparing the response rates of carmustine, dacarbazine, and cisplatin with and without tamoxifen in patients with metastatic melanoma. National Cancer Institute of Canada Clinical Trials Group.

Abstract: These results demonstrate that the addition of high doses of tamoxifen to this chemotherapy regimen does not increase the response rate compared with chemotherapy alone in unselected patients with metastatic melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
1
4

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(69 citation statements)
references
References 7 publications
3
61
1
4
Order By: Relevance
“…In fact, previous reports have repeatedly shown that overall survival is higly risk-dependent (Hoffmann et al, 1998;Rusthoven et al, 1996). This is confirmed by our study since we reported that patients with liver metastases had a significantly shorter survival and shorter progression free survival compared to patients without liver metastases.…”
supporting
confidence: 91%
“…In fact, previous reports have repeatedly shown that overall survival is higly risk-dependent (Hoffmann et al, 1998;Rusthoven et al, 1996). This is confirmed by our study since we reported that patients with liver metastases had a significantly shorter survival and shorter progression free survival compared to patients without liver metastases.…”
supporting
confidence: 91%
“…Our study was set up befoXre the results of the recent randomized study reporting a superior response rate for chemotherapy followed by biotherapy (Legha et al, 1996 (Rusthoven et al, 1996). Very few CRs were reported in that trial (< 5%), and none were detected in our chemotherapy-alone group.…”
Section: British Journal Of Cancermentioning
confidence: 99%
“…One patient on Schedule B reported that she was ceasing treatment after 43 days because of out tamoxifen, but without interferon-a. 6 nausea, vomiting, and malaise. Even though the protocol would not have required tumor measurements unSurvival Failure free and overall survival for all patients entil Week 9, a scan on Day 47 did show PD in her liver; thus, she was considered to have PD.…”
Section: Resultsmentioning
confidence: 99%